ACCOUNTING ADDITIONAL CAPITAL IN COMMERCIAL ORGANIZATIONS - Irina V. Bakholdina (Вестник Северо-Кавказского федерального университета, 2022)
Additional capital is part of the organization's equity, which is the common property of all members of the organization. Therefore, it is important to correctly and properly organize the accounting of its formation and use.